Characterization of Chromatin Remodeling Genes Involved in Thermal Tolerance of Biologically Invasive Bemisia tabaci - Ji, Shun-Xia; Wang, Xiao-Di; Lin, Ze-Kai; Wan, Fang-Hao; Lü, Zhi-Chuang; Liu, Wan-Xue (Frontiers in Physiology, 2022)
As an invasive species, Bemisia tabaci Mediterranean (MED) has notable potential to adapt to a wide range of environmental temperatures, which enables it to successfully spread after invasion and occupy habitats over a wide latitude range. It has been postulated that chromatin remodeling mechanisms are related to the rapid acquisition of adaptive traits and thermal resistance in invasive species; however, relevant experimental evidence is scarce. To identify the molecular characteristics and assess the role of chromatin remodelers in thermal stress within invasive MED and native Asia II 1 of the B. tabaci species complex, we identified 13 switching defective/sucrose non-fermenting (SWI/SNF) and 10 imitation switch (ISWI) family members in the B. tabaci genome, analyzed their molecular characteristics and structures, and identified key mutation sites between MED and Asia II 1, then cloned the catalytic subunits, and revealed the difference in thermal tolerance function. The results showed that the expression levels of Bt-BRM-1 and Bt-BRM-2 were significantly higher in MED than in Asia II 1 during heat stress, and Bt-BRM-2 expression was significantly higher during cold stress. In addition, RNA interference results indicated that the two target genes had similar temperature tolerance function in the both two cryptic species. This study is the first to identify and analyze the molecular characteristics of SWI/SNF and ISWI family members and reveal their potential key roles in temperature tolerance in poikilothermic ectotherms. The results will assist in understanding the underlying temperature adaptation mechanism of invasive insects and will enrich stress adaptation research systems from an epigenetic perspective.